(untitled) (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2019)
This paper explores the relationship between instrumental music training and literacy. Studies referenced in this paper support the positive impact that instrumental music training (such as band) has on literacy rates and learning in general. This relationship was not seen for choral studies but specifically for instrumental music education. When done correctly, music training supports the learning of students and boosts their reading levels. The quality of the music instruction also affects the outcomes. By exploring these studies, this paper argues that quality instrumental music training (i.e., quality band programs) leads to higher literacy rates, as measured by state test scores.